Implementation Of Health Law In Medical Accident Cases By Medical Personnel And Health Personnel To Patients - Rahayu, Tasmi; Permatahati, Vita Setya; Santoso, Aris Prio Agus (VJJ, 2021)
Health has a very important element in a country's progress. Each country seeks to give primary attention to health services, starting from the provision of professional health workers to modern health facilities. Health law basically regulates the rights, obligations, functions, responsibilities of the parties involved in the health sector, and provides certainty of legal protection to recipients and providers of health services. This study aims to determine how the legal protection of patients, doctors and health workers in cases of medical accidents and the legal liability of health care facilities in cases of medical accidents. Medical accidents are unexpected and unexpected events, and there is no more intentional element in the form of planning. This research method uses a sociological juridical approach with primary and secondary data collection. Based on the research results obtained that from some of the answers to the questionnaire there must be full attention to error prevention and patient safety. Encourage patients to play an active and involved role and provide information to the health team. The aim is to highlight specific improvements in patient safety and current problem areas in healthcare. From the results of the study that criminal responsibility is imposed on health workers who make mistakes when carrying out health services/treatments/medical actions in hospitals. Health is regulated in Law No. 36 of 2009, in which there are medical personnel and other health workers. Health worker is every person who devotes himself to the health sector and has knowledge and or skills through education in the health sector which for certain types requires the authority to carry out health efforts.